A latent profile analysis of first-year university students’ academic expectations - Araújo, Alexandra M. (2021)
Academic expectations are an important variable in the explana-tion of adaptation and academic success in higher education. This paper uses latent profile analysis as a person-centered statistical approach to clas-sify students into groups of similar typesof expectations for higher educa-tion, at the beginning of the first year in university. Participants were 2,478 first-year Portuguese students. Based on the scores of seven dimensions of expectations, we identified six classes of students. Most students (84%) presented moderate levels of expectations, while 8% and 4%, respectively, reported very high and low expectations. One class represented a group of students (4%) with high expectations for the quality of education and for political engagement and citizenship and lower expectations for social in-teraction and attending to social pressures. Male and older students showed more positive expectations. Students from privileged family back-grounds are more likely to present higher expectations for political en-gagement and citizenship experiences, and lower expectations for social in-teraction and leisure and attending to social pressures.